Discurso, identidade e subjetividade: uma arquegenealogia da bandeira e das cores nacionais - Sousa, Jacyane Dantas de (2023)
Considering discourse as a strategic place within which power and knowledge relations function, as well as the production of subjectivities, this research proposes to undertake an archegenealogy of the Brazilian flag and national colors as symbols of a national identity and as constitutive elements. of the Brazilian identity device. The intention will be to demonstrate the discursive functioning of such elements through their historical thickness in order to point out the production of subjectivities that result from it, asserting the ideas of nation, nationalism and patriotism. Therefore, we will seek to interrogate the discursive materiality of these Brazilian symbols regarding their historical conditions of emergence, aiming to point out in their functioning the forms of sayability, conservation, memory, reactivation and appropriation of the statements that discursively express them. It is a script that begins with the flag of the Kingdom of Brazil, in 1822, which passes through the Brazilian flag proposed in 1889, popularized by the sports field in the 70s, and which flows into statements produced in our days, particularly those who have been disputing the Brazilian flag in the political field since the so-called June Days, in 2013. Through the proposed path of analysis, and considering that the identity device is composed of heterogeneous elements, the research corpus comprises statements formulated in different discursive genres, such as laws , decrees, news and social media posts. With this, it will be possible to demonstrate the performance of the identity device in our days and, consequently, the production of Brazilian subjects. As a theoretical-methodological foundation, this research starts from Foucauldian Discursive Studies in dialogue with Cultural Studies.